The serum vitamin D status in adults with diabetic retinopathy: A systematic review and meta-analysis: Vitamin D Status in Diabetic Retinopathy: A Meta-Analysis - Wei, Hongyu; Wang, Hao; Diao, Ke; Wang, Xiaoxuan; Chen, Hong; Wang, Congying; Zhang, Minglian (Journal of Medical Biochemistry, 2025)
Background: Emerging evidence suggests that vitamin D may play a crucial role in the development of diabetic retinopathy (DR). However, the extent of vitamin D deficiency in individuals with DR remains uncertain. This study aimed to evaluate serum vitamin D levels in adults with DR.Methods: A comprehensive literature search was conducted using the Embase, PubMed, and Cochrane databases to identify observational studies assessing serum levels of 25(OH)D₃, 1,25(OH)₂D₃, or total 25(OH)D in individuals with DR. A total of 31 independent studies involving 12,227 diabetic individuals were included in the meta-analysis.Results: The pooled mean concentration of total 25(OH)D among individuals with diabetes was 16.04 ng/mL (95% CI: 15.13–16.96; I² = 98.8%), while the mean serum level of 25(OH)D₃ in those with DR was 10.68 ng/mL (95% CI: 5.94–15.41; I² = 99.5%), both significantly below the normal reference range. The average concentration of 1,25(OH)₂D₃ was 31.14 pg/mL (95% CI: 24.35–37.94; I² = 98.8%).Conclusions: Individuals with diabetic retinopathy exhibit significantly reduced levels of vitamin D. These findings support the consideration of vitamin D supplementation in DR management. Further large-scale, prospective studies are needed to clarify the causal relationship between vitamin D and DR.
Keywords: Diabetic retinopathy; Vitamin d; 25-hydroxyvitamin D3; 1,25-Dihydroxyvitamin D3; Meta-analysis